THE ACADEMIC INTEGRITY OF BUDDHIST COLLEGE STUDENTS IN INDONESIA - Ahsanul Khair Asdar; Tri Amiro (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2020)
This study was a descriptive research with the quantitative approach which aimed to describe the academic integrity of the Buddhist college students in Indonesia. This study used 224 students who selected using proportionate cluster sampling. The data were collected using the academic integrity questionnaire with five dimensions, namely honesty, trust, fairness, respect, and responsibility. The questionnaire consisted of 39 items with a Likert modification scale (four options). The result of this study showed that the academic integrity of Buddhist College students in Indonesia was supported by the fairness dimension. The academic integrity both of male and female college students were supported by the fairness dimension, and neither was based on the department, the academic integrity both of Dharmacarya and Dharmaduta students were supported by the fairness dimension. Generally, the academic integrity of Buddhist college students in Indonesia was supported by the fairness dimension which included fairness form lecturers, fairness in expressing opinions, and transparency of the values in the lecture process. Nevertheless, both the honesty and the trust dimension need to be considered because they got a lower score than the other dimensions.